The Artist in the Suit - Grehan, Mary (Irish Journal of Arts Management and Cultural Policy, 2020)
A reflection on the challenge of maintaining an artistic practice while pursuing a career as an arts manager in healthcare. Mary Grehan has spent most of her career as an arts manager bringing arts experiences into hospitals. Although an art college graduate, the demands of her early career quickly overtook her fledgling visual arts practice. Twelve years into her career she resurrected a creative practice in visual art before turning to writing and since that point has juggled the demands of both practices – the day job as an arts manager working in healthcare and the artist in the attic. In this article, she reflects on the different rhythms, cultures and challenges of both practices and how as an arts manager she brokers the relationship between artists and healthcare professionals. She also questions whether her creative practice shapes her as an arts manager.